Effects of single femoral nerve block and continuous femoral nerve block on perioperative analgesia and muscle strength in elderly patients undergoing total knee arthroplasty, a randomized clinical trial - Tao, Yan; Cai, Nan; Zhang, Juxia; Zhou, Yan; Liu, Pengfei (Frontiers in Surgery, 2025)
ObjectiveTo investigate the effect of single femoral nerve block (SFNB) with 0.2% ropivacaine 50 ml on postoperative pain and muscle strength in elderly patients undergoing knee replacement.MethodsNinety-four patients scheduled for primary total knee arthroplasty (TKA) were randomized into two groups. The patients in the SFNB group received SFNB with 50 ml 0.2% ropivacaine (n = 48), while the patients in the continuous femoral nerve block (CFNB) group (n = 46) received CFNB with an initial load of 20 ml 0.5% ropivacaine and a continuous injection of 0.2% ropivacaine at a rate of 5 ml/h. After the surgery, all patients were administered patient-controlled intravenous analgesia. The primary outcome was the visual analogue scale (VAS) score at 24 h postoperatively. The secondary outcomes included: (a) Pain scores at 2 h, 6 h, 12 h, 48 h, and 72 h after surgery, and the total dosage of celecoxib; (b) Muscle strength of the quadriceps at 2 h, 6 h, 12 h, 24 h, 48 h, and 72 h postoperatively; (c) Range of motion (ROM) at 24 h, 72 h, and 1 week after surgery; (d) American Knee Society knee score (AKS) at 1 week postoperatively; (e) Related complications (e.g., nausea and vomiting), and length of hospitalization; (f) General Comfort Questionnaire (GCQ) score at 72 h postoperatively.Results(a) There were no statistically significant differences in VAS scores (p > 0.05) or the total dosage of celecoxib (p > 0.05) between the two groups at various time points; (b) The muscle strength scores in the SFNB group were higher than those in the CFNB group (p < 0.05) at 6 h, 12 h, and 24 h postoperatively; (c) Knee ROM in the SFNB group was better than in the CFNB group (p < 0.05); (d) There were no significant differences in adverse events between the two groups (p > 0.05); (e) The physiological and psychological scores on the GCQ in the SFNB group were higher than those in the CFNB group (p < 0.05).ConclusionSFNB, with 0.2% ropivacaine 50 ml provides effective pain relief, and improves patient comfort after surgery, without increasing adverse effects. SFNB is a safe and convenient option for postoperative pain management following knee surgery.